2016
DOI: 10.48550/arxiv.1603.01336
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Simplified Relative Citation Ratio for Static Paper Ranking: UFMG/LATIN at WSDM Cup 2016

Sabir Ribas,
Alberto Ueda,
Rodrygo L. T. Santos
et al.

Abstract: Static rankings of papers play a key role in the academic search setting. Many features are commonly used in the literature to produce such rankings, some examples are citationbased metrics, distinct applications of PageRank, among others. More recently, learning to rank techniques have been successfully applied to combine sets of features producing effective results. In this work, we propose the metric S-RCR, which is a simplified version of a metric called Relative Citation Ratio -both based on the idea of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…MAG has grown massively from 2015 to 2016 and, according to Wade, Kuasan, Yizhou, and Gulli (2016), it contains approximately 140 million publication records (83) 1 , 40 million authors (20), 3.5 million institutions (0.77), 60,000 journals (22,000), and 55,000 fields of study (50,000). Ribas, Ueda, Santos, Ribeiro-Neto, and Ziviani (2016) found that 59% of the papers in MAG are without citation information. Currently, MAG data can be accessed in three different ways: by using the MA search engine 2 , by downloading historical snapshots of MAG 3 , or by employing the AK API 4 .…”
Section: Academic Knowledge Apimentioning
confidence: 99%
“…MAG has grown massively from 2015 to 2016 and, according to Wade, Kuasan, Yizhou, and Gulli (2016), it contains approximately 140 million publication records (83) 1 , 40 million authors (20), 3.5 million institutions (0.77), 60,000 journals (22,000), and 55,000 fields of study (50,000). Ribas, Ueda, Santos, Ribeiro-Neto, and Ziviani (2016) found that 59% of the papers in MAG are without citation information. Currently, MAG data can be accessed in three different ways: by using the MA search engine 2 , by downloading historical snapshots of MAG 3 , or by employing the AK API 4 .…”
Section: Academic Knowledge Apimentioning
confidence: 99%